Autonomic dysfunction as a mechanism of intradialytic blood pressure instability. Issue 6 (20th July 2017) - Shafi, Tariq; Mullangi, Surekha; Jaar, Bernard G.; Silber, Harry
Abstract: The autonomic nervous system (ANS) is the principal endogenous defense mechanism that maintains blood pressure in the setting of hypotension. Disruption of the ANS impairs this ability and can contribute to blood pressure instability, including hypotension and hypertension. In this narrative review, we provide an overview of the ANS and the consequences of its dysfunction in patients with end‐stage kidney disease treated with dialysis. We also discuss possible mechanisms of this autonomic dysfunction that may need future investigation.